Effectiveness Formulation of Tobacco and Tannin Fermentation Extract against Aphids (Aphis gossypii Glover) on Curly Red Chilli - Latutoibin, Risal; Suwandi, Suwandi; Irsan, Chandra; Harman, Hamidson; Suparman, Suparman; Ahmad , Muslim (BIOVALENTIA: Biological Research Journal, 2024)
Aphids is one of the main pests that attack curly red chili plants. Bioinsecticides can be an alternative to synthetic insecticides in controlling aphids. Tobacco leaf extract and tannin can act as insecticides against various types of insect pests. The aim of this study was to determine the effectiveness of formulations containing fermented mixtures of tobacco leaves and tannin as bioinsecticides against aphids on curly red chili plants. The efficacy experiment was conducted in a greenhouse arranged in a completely randomized design (CRD) with 5 formulation concentration treatments, namely 10%, 5%, 2.5%, 1.25%, and 0% (water), with 5 replications. The treatment was carried out by directly spraying the formulation liquid onto the underside of leaves infested with aphids. The results showed that the tobacco and tannin formulation treatments significantly reduced aphid populations, particularly at the 5% and 10% concentration treatments. The efficacy of population suppression reached 92% after 3 days for the 10% concentration and suppressed the population by 93% after 5 days of application for the 5% concentration. After 7 days of application, the efficacy of aphid population suppression was 99% and 100%, respectively, for the 10% and 5% concentrations. The LT50 values for population suppression occurred after 1.18 and 2.67 days for the 10% and 5% concentrations, respectively. The fermented mixture of tobacco and tannin formulations has the potential to be used as a bioinsecticide for controlling aphids.